Optimalisasi Instagram Sebagai Strategi Digital untuk Produk UMKM Surya Jaya Demak - Denisa Vinka Rudika; Dwi Candra Purnamasari (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
The development of information technology encourages Micro, Small, and Medium Enterprises (MSMEs) to adapt to digital marketing, one of which is through the utilization of Instagram. Although this platform has great potential in accelerating product reach, many MSMEs have not optimized it in an integrated manner in terms of content management and Instagram social media production. This research is motivated by the problems faced by Surya Jaya, an MSME in Demak, which experienced marketing stagnation due to the use of promotional media that lacked layout redesign. An evaluation of the partner's Instagram account revealed a low engagement rate, the absence of communicative content pillars, as well as a monotonous brand visual character that lacked a consistent layout design. Therefore, this research aims to design an Instagram social media management strategy that can support the promotion of the Surya Jaya MSME. The focus of the improvement includes redesigning the visual interface layout on Surya Jaya's Instagram account. The results of this research are expected to provide effective digital marketing management guidelines, produce significant promotional and sales designs, and be able to improve the brand image and expand the sales reach of the Surya Jaya MSME.